Nghiên cứu sử dụng màng tẩm chất lỏng ion cho quá trình tách khí CO2 ra khỏi hỗn hợp với khí metan - Lệ Thủy, Bùi Thị (Vietnam Journal of Chemistry, 2015)
Some supported ionic liquid membranes (SILMs) were prepared from polyvinylidene fluoride (PVDF), polyethersulfone (PES) membranes and ionic liquids butyl methyl imidazolium tetrafluoroborate ([BMIM][BF4]), butyl methyl imidazolium acetate ([BMIM][CH3COO]). Prepared SILMs were used for CO2 separation from the CO2/CH4 gas mixture. The results showed that the ideal selectivity 10.72÷14.43 and the real selectivity 9.77÷12.85 of SILMs for CO2/CH4 were observed (separation yields reached 90÷93 %) The mass and selectivity of SILMs were stable after working continuously for 30 days. These results exhibit the promising potential of using SILMs for CO2 separation processes